Penerapan Aspek Teknis Pemeliharaaan Ternak Kambing Di Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - Tamanian D. F. Sagala; Zulfa Elymaizar; Filawati Filawati (Jurnal Ilmu Peternakan Indonesia, 2026)
Goats are important small ruminants widely raised in tropical regions and contribute significantly to rural livelihoods and local economies. In Jambi Luar Kota District, Muaro Jambi Regency, goats are the most commonly raised small ruminants due to their adaptability, ease of management, and strong market demand. However, the implementation of technical goat husbandry practices remains suboptimal, limiting productivity and the potential economic benefits for farmers.This study was conducted in Jambi Luar Kota District, Muaro Jambi Regency, with research locations selected purposively in Pijoan, Sungai Duren, and Pematang Villages, which have the largest goat populations in the district. Respondents were selected using purposive sampling, consisting of farmers who raised at least five goats. The variables observed included the general characteristics of the study area, farmer profiles, and the implementation of technical aspects of goat husbandry, namely breeding and reproduction, feeding and watering, management practices, housing, and health and disease control. The results showed that most respondents were of productive age (86.79%), had an education level ranging from elementary to senior high school (88.67%), worked primarily as farmers or gardeners (67.92%), and had less than five years of goat farming experience (45.28%). The dominant goat breeds raised were Peranakan Etawah (PE) goats (35.23%), Kacang goats (33.56%), and Rambon/Jawarandu goats (27.74%). The implementation levels of technical husbandry aspects were 63.42% for breeding and reproduction, 62.89% for feeding, 58.49% for management, 74.09% for housing, and 56.35% for health and disease control. Overall, the implementation of technical goat husbandry aspects reached 63.04%, which was categorized as moderate.